Onion storage in tropical region — a review (Current Horticulture, 2024)
Onion (Allium cepa L.) is one of the most widely cultivated vegetable in the world. It is used daily in culinary preparations. Onion is produced mainly in the season in temperate region and one or two or three seasons in tropical region as per the climatic conditions. Thus, a sizable quantity of onion is stored all over the world to fulfill the daily requirements of onion. Onion is generally stored at two temperature and humidity regimes, i.e. 0-2°C and 65-70% RH and 25-30°C and 65-70% RH. In tropical region onion, is stored at ambient conditions in different types of structures. The storage losses in tropical region are very high (30-40%) due to improper pre-and post-harvest management and poor storage environment coupled with climatic conditions. Lot of research works have been carried out in all tropical onion-growing countries on various aspects of storage. The varieties, nutrient management, time, quality and quality of irrigation, time and methods of harvesting, field and shade curing are some important pre-harvest factors effecting storability. Post-harvest treatments such as irradiation, fumigation and storage environment such as type of structure, ventilation pattern, type of construction material, design, stake dimensions, temperature and humidity regime, packing material, season of storage are post-harvest factors effecting storability. The use of recommended varieties, production technologies, curing, ventilated well-designed permanent structure and irradiation may reduce these losses up to 20-25% with economic feasibility. The research works carried out in tropical onion-growing countries is summarized in this review.
Keywords: Onion; Storage; Tropical region; Pre-harvest; Past-harvest; Climatic conditions; Storability